1985
DOI: 10.1111/j.1365-2125.1985.tb05153.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicardipine hydrochloride in essential hypertension‐a controlled study.

Abstract: Fifty patients with mild essential (primary) hypertension entered a double‐blind, parallel‐group study with either nicardipine 30 mg three times daily or placebo, randomly assigned as monotherapy for 6 weeks. At the end of 6 weeks, the nicardipine‐treated group had a statistically significant reduction in mean supine systolic/diastolic pressure of 21.2/15.0 mm Hg (P less than 0.001) compared with the nonsignificant reduction of 0.7/2.9 mm Hg in the placebo‐treated group. The difference in mean response between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Dihydropyridine calcium blockers, rep resented by nifedipine and nicardipine, are widely used for the treatment of hypertensive disorders (1)(2)(3)(4)(5). However the clinical use fulness of these calcium blockers has been limited by dosage frequency because their durations of action are relatively short (6).…”
mentioning
confidence: 99%
“…Dihydropyridine calcium blockers, rep resented by nifedipine and nicardipine, are widely used for the treatment of hypertensive disorders (1)(2)(3)(4)(5). However the clinical use fulness of these calcium blockers has been limited by dosage frequency because their durations of action are relatively short (6).…”
mentioning
confidence: 99%
“…Nicardipine was associated here with a significant increase in heart rate in Group C, but not in Groups A and B. Oral doses of nicardipine [7,25] or nifedipine [26,27] have been reported not to cause any increase in heart rate in patients with essential hypertension, whereas acute intravenous doses of these drugs [12,28] may increase the rate. It has been suggested that the baroreceptor might be reset so that the heart rate would return to normal after chronic treatment with them.…”
Section: Discussionmentioning
confidence: 93%
“…This is in contrast to the experience with a similar dosage of nifedipine, which was effective, but significant side effects were frequent (7). The dosage employed in the present study has been used successfully in clinical trials in the treatment of ischemic heart disease and hypertension (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%